L’universalità e il particolarismo della guerra e della pace. Uno sguardo attraverso i diritti umani - Altini, Carlo (Filosofia Morale/Moral Philosophy, 2022)
A characteristic of philosophical concepts consists in aspiring to universality just as they manage to intercept contingent singularities. This observation is valid not only for theoretical concepts, but also for all those political concepts (democracy, sovereignty, etc.) which have received a decisive elaboration in the philosophical field: this also applies to war and peace. In fact, the advantage of philosophical analysis lies precisely in trying to bring together the universal and the particular. A philosophical analysis of the war/peace dichotomy cannot neglect the comparison with the singularities of these phenomena but – if it does not want to flatten itself on a sociological or political dimension – it cannot even forget their universal foundation.